Effect of Lentinus sajor-caju on the chemical composition and antioxidant activity of highland barley straw under solid-state fermentation - Wang, Yuqiong; Liao, Yangci; Gou, Changlong; Zhang, Hang; Chen, Liming; Bao, Yuhong (Frontiers in Microbiology, 2024)
The efficient utilization of straw resources as animal feed has gained considerable attention. The objective of this study was to evaluate whether Lentinus sajor-caju treatment alters the chemical composition and antioxidant activity of highland barley straw and enhances its functional value as a ruminant feed. Methods: The chemical composition, antioxidant capacity, and metabolomic profile of highland barley straw were determined after 21 days of solid-state fermentation with L. sajorcaju at 25 ℃. The differential metabolites between fermented and unfermented highland barley straw were identified by LC-MS and the relationship between the identified metabolites and antioxidant capacity was elucidated. Results: The results showed that, compared with untreated highland barley straw, the crude protein and ether extract contents were higher (51.55% and 76.43%, respectively) in highland barley straw after 21 days of incubation with L. sajor-caju, whereas the hemicellulose, cellulose, and acid detergent lignin contents were lower (2.48%, 25.08%, and 45%, respectively). The total antioxidant capacity was significantly higher in L. sajor-caju-treated than in untreated highland barley straw. In total, 600 differential metabolites (301 upregulated and 299 downregulated) were identified between L. sajor-caju-fermented and unfermented highland barley straw. Correlation analysis results showed that Fe 2+ scavenging and total phenolic content were strongly correlated with total antioxidant capacity. Meanwhile, the differential flavonoid metabolites between fermented and unfermented highland barley straw were primarily associated with antioxidant activity, with kaempferol 3-xylosylglucoside, isoginkgetin, and rhoifolin being the most representative. Conclusion: Thus, this study demonstrates that L. sajor-caju could enhance the functional value of highland barley straw, showing the potential of L. sajor-caju for improving the utilization of agricultural straws in ruminants.